Biomechanical Evaluation of Different Surgical Approaches for the Treatment of Adjacent Segment Diseases After Primary Anterior Cervical Discectomy and Fusion: A Finite Element Analysis - Ke, Wencan; Chen, Chao; Wang, Bingjin; Hua, Wenbin; Lu, Saideng; Song, Yu; Luo, Rongjin; Liao, Zhiwei; Li, Gaocai; Ma, Liang; Shi, Yunsong; Wang, Kun; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Symptomatic adjacent segment disease (ASD) is a common challenge after anterior cervical discectomy and fusion (ACDF). The objective of this study was to compare the biomechanical effects of a second ACDF and laminoplasty for the treatment of ASD after primary ACDF. We developed a finite element (FE) model of the C2-T1 based on computed tomography images. The FE models of revision surgeries of ACDF and laminoplasty were simulated to treat one-level and two-level ASD after primary ACDF. The range of motion (ROM) and intradiscal pressure (IDP) of the adjacent segments, and stress in the cord were analyzed to investigate the biomechanical effects of the second ACDF and laminoplasty. The results indicated that revision surgery of one-level ACDF increased the ROM and IDP at the C2–C3 segment, whereas two-level ACDF significantly increased the ROM and IDP at the C2–C3 and C7-T1 segments. Furthermore, no significant changes in the ROM and IDP of the laminoplasty models were observed. The stress in the cord of the re-laminoplasty model decreased to some extent, which was higher than that of the re-ACDF model. In conclusion, both ACDF and laminoplasty can relieve the high level of stress in the spinal cord caused by ASD after primary ACDF, whereas ACDF can achieve better decompression effect. Revision surgery of the superior ACDF or the superior and inferior ACDF after the primary ACDF increased the ROM and IDP at the adjacent segments, which may be the reason for the high incidence of recurrent ASD after second ACDF.